Effect of Service Quality, Online Advertising, and Learning Innovation on Customer Satisfaction Through Brand Image at Course Institutions in Tangerang City - Rudianto Rudianto; Sutisna Sutisna; Uli Wildan Nuryanto (LPPPIPublishing, 2023)
The purpose of this research is to analyze effect of service quality, online advertising, and learning innovation on customer satisfaction through brand image at Course Institutions in Tangerang City. This research approach uses quantitative research. The population of training participants in Tangerang City as many as 475 people. Based on the calculation, the number of samples to be taken is 221 people. Data analysis using inductive data analysis method. The results of the study show that service quality has a significant effect on brand image at Course Institutions in Tangerang City. Online advertising has no significant effect on brand image at Course Institutions in Tangerang City. Learning innovation has a significant effect on brand image at Course Institutions in Tangerang City. Service quality has a significant effect on customer satisfaction at Course Institutions in Tangerang City. Online advertising has no significant effect on customer satisfaction at Course Institutions in Tangerang City. Learning innovation has a significant effect on customer satisfaction at Course Institutions in Tangerang City. Brand image has a significant effect on customer satisfaction at Course Institutions in Tangerang City. Brand image is able to significantly moderate service quality on customer satisfaction at Course Institutions in Tangerang City. Brand image is not able to significantly moderate online advertising on customer satisfaction at Course Institutions in Tangerang City. Brand image is able to significantly moderate learning innovation on customer satisfaction at Course Institutions in Tangerang City.